Gümrük vergi̇ cezaları sebepleri̇, anali̇zleri̇ ve örnekler - Özer, Elif (My University, 2023)
Gümrük vergileri, gümrük idareleri tarafından, ithalat ve ihracata tabi tutulan eşyaya ilişkin olarak tahakkuk ve tahsil edilen vergi türüdür. Bu doğrultuda, 4458 sayılı Gümrük Kanunu kapsamında gümrük vergilerinin usul ve esasları tanzim edilmiştir. Gümrük mevzuatına uygun şekilde hareket edilmediğinde gümrük idaresince, 4458 sayılı Gümrük Kanunu hükümlerine göre işlem tatbik edilerek Ceza Kararları düzenlenmektedir. 4458 sayılı Gümrük Kanunu ikinci bölümünde yer alan Vergi Kaybına Neden Olan İşlemlere Uygulanacak Cezalar kapsamı 234, 235, 236, 237, 238 ve üçüncü bölümünde yer alan Usulsüzlüklere İlişkin Cezalar 239. ve 241. maddeleri hükmünce gümrük idaresini vergi kaybına uğratan durumlarda gümrük cezaları düzenlenir. Literatüre bakıldığında Gümrük Cezaları ile ilgili genel anlamda ceza düzenlendikten sonraki durumun incelendiği görülmektedir. Gümrük idaresince ceza düzenlenmesinin ardından idari itiraz yolu, dava aşamaları, uzlaşma ve çözüm yolları, zamanaşımı sorunu, hukuki boyutu gibi aşamalar üzerinde çalışılmıştır. Ancak gümrük cezalarının sebeplerinin araştırıldığı, hatanın nerden/ kimden kaynaklandığının ve firmaların nerede hata yaptıklarının incelendiği bir araştırmaya rastlanılamamaktadır. Bu çalışmada, gümrük vergi cezalarının dayanakları, sebepleri, örneklerle açıklanarak analiz edilmiştir. Gümrük idaresinin vergi cezası düzenlerken dayanak aldığı kanunlar ve maddeleri incelenerek, söz konusu cezaların meydana gelme sebepleri incelenmiştir. Diğer taraftan, cezadan sorumlu tutulan ithalatçı/ ihracatçı firmaların vergi cezasına konu olacak bir fiilde bulunması halinde, yükümlüsünce yapılan hatalar (mevzuatın karmaşık yapısı, işi takip eden personelin bilgi eksikliği vb. gibi) analiz edilerek, söz konusu firmaların ceza almalarına neden teşkil eden hataların nereden ve kimden kaynaklandığı belirlenmiştir

Custom duties are the type of tax accrued and collected by the customs administrations regardingthe goods subject to import and export. In this direction, the procedures and principles of custom taxes have been regulated within the scope of the Customs Law No. 4458. When the custom legislation is not acted upon, Penal Decisions are issued by the custom administration by applying the procedure in accordance with the provisions of the Customs Law No. 4458. Custom penalties are regulated in accordance with Articles 234, 235, 236, 237, 238, 239 and 241 of the Customs Law No. 4458. Looking at the literature, it is seen that the situation after the regulation of the custom penalties in general terms is examined. After arranging a penalty by the customs administration, stages such as administrative objection, litigation stages, reconciliation and solution ways, the problem of statute of limitations, and its legal dimension have been studied. However, no research can be found in which the reasons for the custom penalties are investigated, where/ who caused the error and where the companies made mistakes. In this study process, a comprehensive literature search will be conducted, the resources related to the subject will be scanned and the laws that form the basis of the Custom law and custom penalties will be discussed in detail. The details of the custom procedures will be explained by interviewing the personnel in various titles in the custom administration. The reasons for the custom penalties will be revealed by interviewing the customs consultancy companies operating in Istanbul, which has the largest customs administrations in Turkey. In this study, the basis and reasons of customs tax penalties were analyzed by explaining with examples. By examining the laws and articles on which the customs administration is based on tax penalties, the reasons for the occurrence of these penalties are examined. On the other hand, if the importer/ exporter companies that are held responsible for the penalty commit an act that will be subject to a tax penalty, the errors made by the liable parties are analyzed and it is determined from where and from whom the errors that cause the said companies to be penalized.
Keywords: Custom Penalties; Custom Taxes; Customs administration; Gümrük Cezaları; Gümrük idaresi; Gümrük Kanunu; Gümrük Vergileri Custom Law; Law and legislation; Turkey; Türkiye; Yasa ve yasama